Building services handbook - Hall, Fred (Elsevier, 2007)
Building Services Handbook summarises the application of all common elements of building services practice, technique and procedure, to provide an essential information resource for students and engineers working in the industry. Information is presented in the highly illustrated and accessible style of the best-selling companion title Building Construction Handbook